2022
DOI: 10.1039/d2nj04417j
|View full text |Cite
|
Sign up to set email alerts
|

Direct α-methylenation of triazines to terminal olefins with DMA

Abstract: We report an efficient metal (Cu or Ni) -catalysed α‑Methylenation of triazines to terminal olefins using DMA as one carbon source. Various substituted triazine derivatives are suitable for this reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Initially, 1a was activated by a hydrogen proton to give 1a' [24][25][26]28], which subsequently reacted with CuX2 to afford I and II [33]. Then, the reaction between II and H2O generating III and IV (IV-1 or IV-2 was formed through the reductive elimination process [14,[36][37][38]. In the presence of metal catalyst, oxygen, or sodium nitrite [39][40][41][42][43][44][45][46][47][48], IV (IV-1 or IV-2) underwen dehydrogenation to afford the desired product 2a [41,[46][47][48] (Scheme 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially, 1a was activated by a hydrogen proton to give 1a' [24][25][26]28], which subsequently reacted with CuX2 to afford I and II [33]. Then, the reaction between II and H2O generating III and IV (IV-1 or IV-2 was formed through the reductive elimination process [14,[36][37][38]. In the presence of metal catalyst, oxygen, or sodium nitrite [39][40][41][42][43][44][45][46][47][48], IV (IV-1 or IV-2) underwen dehydrogenation to afford the desired product 2a [41,[46][47][48] (Scheme 3).…”
Section: Resultsmentioning
confidence: 99%
“…In this transformation, water participates in the reaction and offers the oxygen for the process with a palladium catalyst, producing phenyl(pyridin-2-yl)methanone in 44% yield, which inspires us to take water as an oxygen donor for an oxidation reaction in the presence of non-noble metals. More recently, our research group has reported a copper-catalyzed synthesis of aroyl triazines and terminal olefin-substituted triazines [36,37]. Surprisingly, in our attempt to obtain N 2 ,N 2 -dimethyl-N 4 -phenyl-6-(1-(pyridin-2-yl)vinyl)-1,3,5-triazine-2,4-diamine, the corresponding oxidation product was observed instead, so we proved that water can provide oxygen for the curtain oxidation transformation.…”
Section: Introductionmentioning
confidence: 99%
“…The initial compound 1 was prepared as referred to in our previous work [38,39,45]. Sodium (2.5 eq) was added to anhydrous MeOH at 0 • C until the sodium was completely consumed.…”
Section: General Procedures For the Synthesis Ofmentioning
confidence: 99%
“…More recently, Cui and their group reported the efficient copper-catalyzed sulfonamidation of arenes via C-H activation, with triazine as the directing group [34]. Inspired by our previous work [35][36][37][38][39], we reasoned that N-aryl-triazines are suitable substrates for the synthesis of indole-substituted triazines through C-H activation. We herein describe the ruthenium-catalyzed synthesis of N-triazine-substituted indoles from N-aryl-triazines and alkynes.…”
Section: Introductionmentioning
confidence: 96%